Using Person-Centered Learning Technologies In Elementary Technology Classrooms - Rasulova Sanobar Mamatkulovna (Genius Publishing Group, 2024)
This article discusses the ways of using student-oriented educational technologies in elementary grades.
Keywords: personality; types of education; technology